Gestational diabetes mellitus seems to be associatied with inflammation - Ayla Aktulay; Yaprak Engin-Ustun; Mehmet Sahin Ozkan; Salim Erkaya; Mustafa Kara; Oktay Kaymak; Nuri Danisman (Acta Clinica Croatica, 2015)
The aim of this study was to investigate whether gestational diabetes mellitus (GDM) is associated with inflammation by comparing serum levels of human chitinase-3-like protein 1 (YKL-40), neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR). This case control study included 29 pregnant women with GDM and 29 pregnant women with normal glucose tolerance matched for age (±2 years) and pre-pregnancy body mass index (±2 kg/m2). The YKL-40/CHI3L1 levels were measured, and NLR and PLR investigated. There were no statistically significant differences in maternal age, gestational age, gravidity and parity. Higher YKL-40 levels were recorded in pregnant women with GDM compared to control subjects (203 (65-300) ng/mL vs. 159.2 (14-290) ng/mL, p=0.007). NLR and PLR were significantly higher in GDM compared with control group. In conclusion, GDM is associated with high levels of YKL-40, NLR and PLR, which indicate inflammatory status.